Branched-Chain Amino Acid Catabolism and Cardiopulmonary Function Following Acute Maximal Exercise Testing in Adolescents - Gumus Balikcioglu, Pinar; Ramaker, Megan E.; Mason, Kelly A.; Huffman, Kim M.; Johnson, Johanna L.; Ilkayeva, Olga; Muehlbauer, Michael J.; Freemark, Michael; Kraus, William E. (Frontiers in Cardiovascular Medicine, 2021)
Background: To provide energy for cardiopulmonary function and maintenance of blood glucose, acute aerobic exercise induces lipolysis, fatty acid oxidation (FAO), glycolysis, and glycogenolysis/gluconeogenesis. These adaptations are mediated by increases in cortisol, growth hormone (GH), and catecholamines and facilitated by a decline in insulin. Branched-chain amino acids (BCAA) also undergo catabolism during intense exercise. Here we investigated the relationship between BCAA catabolism and metrics of cardiopulmonary function in healthy, well developed, mature adolescent athletes undergoing an acute bout of maximal aerobic exercise. Hypothesis: We hypothesized: (a) acute maximal exercise in adolescents induces lipolysis, FAO, and BCAA catabolism associated with increases in growth hormone and cortisol and a reduction in insulin; (b) increases in GH are associated with increases in ghrelin; and (c) metrics of cardiopulmonary function (aVO2, rVO2, aVO2/HR max) following maximal exercise correlate with increases in GH secretion, FAO, and BCAA catabolism. Methods: Blood samples before and after maximal cardiopulmonary exercise in 11 adolescent athletes were analyzed by tandem-mass spectrometry. Paired, two-tailed student’s t-tests identified significant changes following exercise. Linear regression determined if pre-exercise metabolite levels, or changes in metabolite levels, were associated with aVO2, rVO2 and aVO2/HR max. Sex and school of origin were included as covariates in all regression analysis. Results: Following exercise there were increases in GH and cortisol, and decreases in ghrelin, but no changes in glucose or insulin concentrations. Suggesting increased lipolysis and FAO, the levels of glycerol, ketones, β-Hydroxybutyrate, and acetylcarnitine concentrations increased. Pyruvate, lactate, alanine and glutamate concentrations also increased. Plasma concentrations of valine (a BCAA) declined (p=0.002) while valine degradation byproducts increased in association with decreases in urea cycle amino acids arginine and ornithine. Metrics of cardiopulmonary function were associated with increases in propionylcarnitine (C3, p=0.013) and Ci4-DC/C4-DC (p<0.01), byproducts of BCAA catabolism. Conclusions: Induction of lipolysis, FAO, gluconeogenesis, and glycogenolysis provides critical substrates for cardiopulmonary function during exercise. However, none of those pathways were significantly associated with metrics of cardiopulmonary function. The associations between rVO2, and aVO2/HR max and C3 and Ci4-DC/C4-DC suggest that the cardiopulmonary response to maximal exercise in adolescents is linked to BCAA utilization and catabolism.